2021
DOI: 10.35730/jk.v12i1.788
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Mobile Technology Dan Penelitian Partisipatoris Untuk Pencegahan Droup-Out Kb Selama Pandemi Covid-19

Abstract: Latar Belakang Masalah: Pada masa pandemi COVID-19, Pasangan Usia Subur (PUS) di Indonesia mengalami hambatan untuk melakukan kunjungan di fasilitas kesehatan dikarenakan pembatasa sosial, hal ini juga mempersulit PUS mengakses kontrasepsi. Data menunjukkan bahwa pada rentang Maret sd Mei 2020, terdapat peningkatan jumlah kehamilan di Indonesia. Penelitian ini bertujuan untuk mencegah drop out KB pada PUS selama masa pandemi COVID-19 dengan menggunakan mobile technology dan PAR serta menggali pengalaman stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…One of the considerations that influence the decision to use contraception is the characteristics of the partner (Harzif et al, 2022). Research result of Astuti (2021) it was found that decision-making related to contraception was carried out jointly by the partner so that an agreement was created between husband and wife in family planning, but did not rule out the possibility that the first decision rested with the husband. In addition, autonomy in family planning is also a strength in decision making which is a dimension of empowering women in the household (Aprillia et al, 2023).…”
Section: Family Planning In Using Contraception or Choosing Tomentioning
confidence: 99%
“…One of the considerations that influence the decision to use contraception is the characteristics of the partner (Harzif et al, 2022). Research result of Astuti (2021) it was found that decision-making related to contraception was carried out jointly by the partner so that an agreement was created between husband and wife in family planning, but did not rule out the possibility that the first decision rested with the husband. In addition, autonomy in family planning is also a strength in decision making which is a dimension of empowering women in the household (Aprillia et al, 2023).…”
Section: Family Planning In Using Contraception or Choosing Tomentioning
confidence: 99%
“…Furthermore, recent research has discovered support from partners, such as the husband's participation in household work and decision-making since the perinatal period and family planning. It can increase women's awareness of the right to use contraception (Astuti et al, 2021). The Indonesian government has performed several steps to increase the number of family planning acceptors as regulated in the Regulation of the Head of the Population and Family Planning Agency National Number 22 of 2017 concerning Postpartum and Post-Miscarriage Family Planning Services, one of which is by issuing a reverse decision-making tool which was developed together with WHO that can be employed during counseling so that mothers and husbands better understand information about contraception which is clear and concise about their rights and can decide their need for contraception (BKKBN, 2022).…”
Section: Decision-making Autonomymentioning
confidence: 99%
“…Moreover, suppose teenage pregnancy occurs outside of marriage and is not desired. In that case, it will also bring consequences of unpreparedness to become a mother and wife, unplanned marriage, and unpreparedness to live a married life (Astuti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Disamping itu, banyak kekhawatiran yang terjadi di masyarakat terutama ibu hamil, sehingga ibu hamil pun tidak dapat mengakses pelayanan kesehatan, begitu pun ibu nifas, bayi balita dan ibu yang menjadi akseptor Keluarga Berencana (KB). Data terakhir dari Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN), menunjukkan adanya penurunan pelayanan KB dari bulan Februari ke Maret yang terjadi secara nasional, hampir 50% pelayanan KB dimasing-masing jenis KB menurun, salah satu faktor nya adalah kurangnya informasi dan edukasi kepada masyarakat, bagaimana berkontrasepsi yang aman saat masa pandemi ini (Astuti et al, 2021).…”
Section: Pendahuluanunclassified